Tumor survivin is downregulated by the antisense oligonucleotide LY2181308: a proof-of-concept, first-in-human dose study. - Talbot, D; Ranson, M; Davies, J; Lahn, M; Callies, S; André, V; Kadam, S; Burgess, M; Slapak, C; Olsen, A; McHugh, P; de Bono, J; et al. (2010)
PURPOSE: Enhanced tumor cell survival through expression of inhibitors of apoptosis (IAP) is a hallmark of cancer. Survivin, an IAP absent from most normal tissues, is overexpressed in many malignancies and associated with a poorer prognosis. We report the first-in-human dose study of LY2181308, a second-generation antisense oligonucleotide (ASO) directed against survivin mRNA. PATIENTS AND METHODS: A dose-escalation study evaluating the safety, pharmacokinetics, and pharmacodynamics of LY2181308 administered intravenously for 3 hours as a loading dose on 3 consecutive days and followed by weekly maintenance doses. Patients were eligible after signing informed consent, had exhausted approved anticancer therapies and agreed to undergo pre- and posttreatment tumor biopsies to evaluate reduction of survivin protein and gene expression. RESULTS: A total of 40 patients were treated with LY2181308 at doses of 100 to 1,000 mg. Twenty-six patients were evaluated at the recommended phase 2 dose of 750 mg, at which level serial tumor sampling and [(11)C]LY2183108 PET (positron emission tomography) imaging demonstrated that ASO accumulated within tumor tissue, reduced survivin gene and protein expression by 20% and restored apoptotic signaling in tumor cells in vivo. Pharmacokinetics were consistent with preclinical modeling, exhibiting rapid tissue distribution, and terminal half-life of 31 days. CONCLUSIONS: The tumor-specific, molecularly targeted effects demonstrated by this ASO in man underpin confirmatory studies evaluating its therapeutic efficacy in cancer.